Pengaruh Debt Covenant, Tunneling Incentive dan Thin Capitalization Terhadap Transfer Pricing dengan Moderasi Tax Minimization - Siska Aprilia Rahmawati; Nera Marinda Machdar (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Today, world economic growth is driven by globalization. With globalization, cross-border transactions increase, which allows investments, goods, and services between countries to become easier. By using transfer pricing methods, businesses can reduce their tax payments. This research aims to study how debt arrangements, tunneling incentives, and thin capitalization impact transfer pricing and tax minimization. The objective is to determine whether the effect of debt is strengthened or weakened by these arrangements. This study conducted qualitative descriptive research. Data collection was done through literature study. The results show that debt convenant, tunneling incentive, and thin capitalization have a significant positive effect on transfer pricing. Tax minimization is able to strengthen the influence of debt convenant, tunneling incentive, and thin capitalization on transfer pricing.